Epidemiology of haemotropic Mycoplasma ovis in selected small ruminant flocks and host cell responses of mice to M. ovis infection - Paul, Bura Thlama (2021)
Haemotropic Mycoplasma ovis is an emerging zoonotic epierythrocytic parasitic bacterium that causes haemolytic anaemia, decreased production outcomes and mortality in sheep and goats. Isolated clinical cases of haemotropic mycoplasmosis have been documented in Malaysian small ruminants since the early 1990s and recent survey of selected flocks in Selangor also reported an association between M. ovis and a severe nematode worm burden in goats. Although the assay of acute-phase proteins and cytokines offers cheaper and sensitive alternatives as early markers of infection, their role in haemoplasma diagnosis is unknown. This study was designed to investigate the epidemiology of M. ovis in selected small ruminant flocks and determine the clinical responses of cytokines, acute-phase proteins, and female reproductive hormones in mice model. Samples and data were collected by crosssectional survey of 5 flocks in Negeri Sembilan, Malaysia. Giemsa-stained blood smears were examined to detect M. ovis and classify infection severity as mild (1-29% infected red cells), moderate (30-59%) or severe (>60%) and microhaematocrit centrifugation was used to determine PCV. Sodium chloride floatation was used for detection of GIP followed by McMaster faecal egg count (FEC) to classify infection severity as mild (50-799), moderate (800-1200) or severe (>1200). Laboratory mice (n=24) were inoculated with mild (1-29%), moderate (30-59%) and severe (>60%) doses of M. ovis and observed for weekly changes in PCV and parasitaemia. Serum samples obtained after euthanasia were used for quantitative ELISA assay of inflammatory and reproductive markers while organ samples were processed by routine H&E staining. Examination of blood smears revealed an overall M. ovis prevalence of 50.7% with a higher risk among breeds, pregnant and lactating animals. Faecal analysis revealed 82.2% incidence of GIP, especially Strongyle/Coccidia (50.9%) co-infection with different patterns of EPG and OPG in among small ruminants. There was a higher incidence of mild GIP infections and M. ovis/Mixed GIP (24.9%) was associated with a lower mean PCV. A higher mean parasitaemia was observed in the co-infections of M. ovis/Mixed GIP (29.72±2.02) and a lower mean PCV coincided with severe M. ovis or nematode infection (25.23±0.741). Mean PCV correlated negatively with EPG output (r = -0.214, p=0.002) and parasitaemia (p= 0.0009, r=-0.18). M. ovis cells appeared in the blood films within one-week and reached a dose-dependent peak parasitaemia in the 4th-week pi with a significant and dose-dependent drop in PCV at weeks 2 & 3 post infection (pi). The serum concentration of haptoglobin (Hp) decreased significantly (p<0.05) by 48.7% in GPsevere (3.92±0.95 μg/ml) compared to the GP-control (7.6±0.9μg/ml), while serum amyloid A (SAA) increased significantly (p<0.05) by 89% in the severe infection group (16.8±1.2μg/ml) compared to the GP-control (8.9±2.4μg/ml). Serum progesterone increased significantly (p<0.05) by 166% in GP-severe (27.4±1.0ng/ml) and 96% in GP-moderate (20.2±2.4ng/ml) while oestrogen levels decreased significantly (p<0.05) by 52.9% in the GP-severe (10.38±2.3ng/ml) than the GPcontrol (22.1±0.6ng/ml). The ovary in GP-severe showed mild leucocytic infiltration, vacuolation and hypertrophy of lutein cells. In the spleen, there were extensive haemorrhage, hypercellularity, infiltration of neutrophils and macrophages in the red pulp. In the lymph node, there was congestion with diffused cellular hyperplasia while the liver showed increased size and number of Kupffer cells, congestion of sinusoid, diffused necrosis of hepatocytes and leucocytic infiltration. The kidneys showed a severe proliferative lesion in the glomerulus, leucocytic infiltration and congestion of the renal veins. Haemotropic M. ovis and gastrointestinal parasites were common in the study area and the risk of M. ovis infection depends on the breed and physiological status of small ruminants. Dysregulated secretions of female reproductive hormones, changes in acute phase proteins, and the cellular changes in the ovary are novel aspects of this study which shades light on the pathogenic mechanisms of haemoplasma infection.